No one is safe until everyone is safe: Direction régionale de santé publique de Montréal’s risk-based approach to multilingual crisis communication - Serrano, María Sierra Córdoba (Revista de llengua i dret, 2025)
Canada’s multiculturalism is situated within a bilingual framework that often restricts Canada’s linguistic diversity, which goes beyond its official languages. The limitations of this framework were exposed by the COVID-19 pandemic, during which government-led crisis communication strategies were guided by the country’s multilingual reality and the risks associated with ignoring it. This article focuses on a case study that examines multilingual communication strategies and practices coordinated during the pandemic by the Direction régionale de santé publique de Montréal. Drawing on documentary evidence and semi-structured interviews, the article reveals that Santé publique Montréal integrated a multilingual approach into its emergency communication strategy after the first wave of the pandemic, which resulted in more translations of COVID-19 information, and the implementation of bottom-up communication practices in collaboration with community-based organisations to build trust. The article also shows that the pandemic paved the way for a risk-based approach to language management capable of helping us rethink multilingualism management in Canada and beyond. La multiculturalitat canadenca se situa en un marc bilingüe que sovint restringeix la diversitat lingüística del Canadà, la qual va més enllà de les seves llengües oficials. Les limitacions d’aquest marc es van fer evidents amb la pandèmia de la COVID-19, durant la qual les estratègies governamentals de comunicació de la crisi es regien per la realitat multilingüe del país i els riscos associats a ignorar aquesta realitat. Aquest article se centra en un estudi de cas que examina les estratègies i les pràctiques de comunicació multilingüe coordinades durant la pandèmia per la Direcció Regional de Salut Pública de Montreal. A partir de proves documentals i entrevistes semiestructurades, l’article revela que Salut Pública de Montreal va integrar una perspectiva multilingüe en la seva estratègia de comunicació d’emergències després de la primera onada de la pandèmia, que es va traduir en més transmissions d’informació de la COVID-19, i la implantació de pràctiques comunicatives de baix a dalt en col·laboració amb entitats comunitàries per generar confiança. L’article també mostra que la pandèmia va preparar el terreny per a una estratègia de gestió lingüística basada en els riscos capaç d’ajudar-nos a replantejar la gestió del multilingüisme al Canadà i en altres llocs. La multiculturalidad canadiense se sitúa en un marco bilingüe que a menudo restringe la diversidad lingüística de Canadá, que va más allá de sus lenguas oficiales. Las limitaciones de este marco se hicieron evidentes con la pandemia de la COVID-19, durante la que las estrategias gubernamentales de comunicación de la crisis se regían por la realidad multilingüe del país i los riesgos asociados a ignorar esta realidad. Este artículo se centra en un estudio de caso que examina las estrategias i las prácticas de comunicación multilingüe coordinadas durante la pandemia por la Dirección Regional de Salud Pública de Montreal. A partir de pruebas documentales y entrevistas semiestructuradas, el artículo revela que Salud Pública de Montreal integró una perspectiva multilingüe en su estrategia de comunicación de emergencias después de la primera ola de la pandemia, que se tradujo en más transmisiones de información sobre la COVID-19, y la implantación de prácticas comunicativas de abajo arriba en colaboración con entidades comunitarias para generar confianza. El artículo también muestra que la pandemia preparó el terreno para una estrategia de gestión lingüística basada en los riesgos capaz de ayudarnos a replantear la gestión del multilingüismo en Canadá y en otros lugares.